Direitos humanos : universalidade e multiculturalismo - Castro, Ana Luiza Moro de (2020)
Human rights have universality as one os its main requirements. At the same time, universality has always been one of its main challenges. We’ll begin our work by demonstrating the modern idea of natural law as the origin of what is known today as human rights. We’ll also debate the difficulties in making natural law compatible with social rights. Soon after, the philosophy of Kant will be used to justify human liberty and, consequently, human dignity. With the philosophy of Arendt, we’ll debate that in order to protect human dignity, it s also necessary to endure that the people are able to take part in public affairs. Finally, multiculturalism will be presented as having the ability to enable a more inclusive and emancipatory content to human rights., as well as granting human rights greater legitimacy